Rare cases of a second recurrence of nephroblastoma with MLLT1 gene mutation: case report and literature review - Dai, Yiling; Chen, Xin; He, Guoqian; Gao, Ju; Guo, Xia (Frontiers in Oncology, 2024)
Nephroblastoma or Wilms tumor is the most common tumor of the urinary system in childhood. The survival rate can reach more than 90% after multidisciplinary treatment, but there is still a certain recurrence rate. In recent years, domestic and foreign scholars have analyzed the gene mutations related to the recurrence of nephroblastoma from the genetics or epigenetics perspective. However, few reports on the relationship between MLLT1 and the pathogenesis have been reported; patients with MLLT1 gene mutations are often associated with poor prognosis. In this case, we report the recurrence of nephroblastoma with MLLT1 gene mutation and review relevant literature. The studies on molecular genetic mechanism will provide a theoretical basis for early warning, optimize individualized treatment plan, and are important for improving prognosis.